FAILURE OF EMPLOYEE RETENTION AND ITS CONSEQUENCES ON ORGANISATION THROUGH CONTENT ANALYSIS - Banerjee, Archita (International Journal of Research -GRANTHAALAYAH, 2019)
For any organization its workforce are the most valuable assets. Their implication to system describes not only the requirement to pull the best competence but also the need to hold on to them for a long term. With evolution of globalization, competition is becoming keener and keener in most industries. These conditions affect the employment in the notion that companies insist on human capital to sustain in the market for a longer period of time. A proper retention strategy improves the performance of organisation in terms of product quality and profitability ratio. The biggest challenge in current work scenario is how to engage people on the job as long as possible by carving a proper career path for them and shaping their future prospects in job. The concept of employee retention is mainly motivating employees to stay in an association for a maximum period of time (Bidisha etal 2013). As Mita (2014) defined employee retention “is a tool accepted by companies to maintain an efficient fleet of workers and consecutively meet functional requirements Based on actual facts and findings, retaining the best employees makes sure client satisfaction, increase in product sales, peer satisfaction and effective succession planning. An entrenched organizational knowledge and learning which means, imparting proper training time and investment on regaining lost knowledge of employees, helps gaining back job security and a costly employee is won back. Thus, failing to which leads to a loss of important employees. A range of approximation suggests that losing a middle manager in most organizations costs up to five times his salary. Corporate were facing lot of problems in retention of employees these days. To hire well-informed people for the job is essential for an employer, but retention is even more important than hiring.